Influence of injection timing and split injection strategies on performance, emissions, and combustion characteristics of diesel engine fueled with biodiesel blended fuels - How, Heoy Geok; Masjuki, Haji Hassan; Kalam, Md. Abul; Teoh, Yew Heng (Elsevier, 2018)
Biodiesel can be used as alternative to replace fossil diesel. However, usage of biodiesel in an unmodified diesel engine can cause higher in nitrogen oxides (NOx) emission. In order to reduce the harmful emission, certain injection strategies can be carried out. In this paper, the effects of biodiesel blends, fuel injection timing and split injection schemes on the engine performance, emissions and combustion characteristics of a medium-duty diesel engine are investigated. Parametric studies relating with start of injection timing variation and multiple injection schemes using B20 and B50 biodiesel blends were performed and benchmarked with petroleum diesel fuel as baseline. A remarkably lower NOx level below 100 ppm can be obtained by retard start of injection (SOI) timing for both of the B20 and B50 fuel operations and with triple injection scheme. It was found that with the use of B50, simultaneous NOx and smoke suppression from the levels of petroleum diesel fuel is attainable in parallel with the implementation of late SOI timing and triple injection scheme in a diesel engine. In conclusion, multiple split injections is a practical strategies to simultaneously decrease NOx and smoke emissions when the SOI timing is fine-tuned and is an ideal alternative to operate with biodiesel fuel.